2006
DOI: 10.1002/path.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin overexpression cooperates with p53 mutation and osteopontin overexpression, and is associated with tumour progression, early recurrence, and poor prognosis in hepatocellular carcinoma

Abstract: Stathmin, a major microtubule-depolymerizing protein, is involved in cell cycle progression and cell motility. This study aimed to elucidate its role in the progression, early tumour recurrence (ETR), and prognosis of hepatocellular carcinoma (HCC). Stathmin mRNA was overexpressed in 88/156 (56%) resected, unifocal, primary HCCs, while p53 mutation was present in 72 (46%) and osteopontin mRNA overexpression in 79 (51%). Stathmin mRNA expression exhibited high concordance (93%) with protein expression in 107 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
128
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 63 publications
7
128
1
Order By: Relevance
“…More importantly, it was to note that STMN1 overexpression has been associated with poor survival of cancers, including colorectal cancer, hepatocellular carcinoma, and oral squamous-cell carcinoma. 5,9,13,14 We demonstrated that overexpression of STMN1 was an independent prognostic factor for survival in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it was to note that STMN1 overexpression has been associated with poor survival of cancers, including colorectal cancer, hepatocellular carcinoma, and oral squamous-cell carcinoma. 5,9,13,14 We demonstrated that overexpression of STMN1 was an independent prognostic factor for survival in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of several molecules and the biological features involved in malignant transformation from dysplastic nodules to HCC have been reported, though the exact genetic mechanism remains to be explored. [23][24][25] Recently, several studies have also shown EZH2 to be highly expressed in aggressive tumors, including human breast cancer, prostate cancer and lymphomas. 9,[13][14][15]26,27 The present study showed PcG proteins Bmi1 and EZH2 which are epigenetic chromatin modifier involved in cancer development, 7 to be involved in this malignant progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in HCCs, elevated stathmin expression has been linked to increased tumor size, the presence of vascular invasion, intrahepatic metastasis, and decreased patient survival. 6 Microtubule destabilizing factors represent potential therapeutic target structures, because reduced but also increased stathmin bioavailability sensitizes tumor cells to treatment with chemotherapeutic agents. 4,7 So far, the regulation of stathmin has been attributed to the modulation of chromatin structure by enhancer of zeste homologue 2 (EZH2), 8 posttranscriptional silencing by the small noncoding RNA miR-223, 9 as well as the expression of the tumor suppressor gene p53.…”
mentioning
confidence: 99%